2020
DOI: 10.15406/ghoa.2020.11.00441
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Helicobacter pylori infection and gastric preneoplastic lesions in patients admitted for upper gastro-intestinal endoscopy in Cotonou (Benin Republic)

Abstract: Infection with Helicobacter pylori (H. pylori) is common in developing countries such as Benin. This germ can cause several gastroduodenal diseases such as gastritis, ulcer, adenocarcinoma or gastric MALT lymphoma. This study aimed to determine the prevalence of H. pylori infection and gastric pre-neoplastic histological lesions in patients admitted for upper gastrointestinal endoscopy (UGE) and to identify factors associated with this infection.Methods: This was a cross-sectional descriptive and analytical st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Furthermore, a prevalence of 64.6% in children with risk factors of overcrowding, patronizing of food vendors, and illiteracy was reported in Egypt [36]. In the Republic of Benin, a 71.5% prevalence rate was reported but was not associated with age, sex, marital status, religion, occupation, or education [37]; 73.2% in Cameroon with a significant association with age, socioeconomic status, alcohol, family history, and nonsteroidal anti-inflammatory drugs and similarly anemia, duodenal ulcer, and chronic gastritis have been reported as common in patients with H. pylori infection [38]; and 71.43% prevalence rate was published in Algeria [39]. In a research conducted in Ethiopia, 88.9% H. pylori prevalence was reported in male individuals, while 82.8% was in female individuals [40].…”
Section: Epidemiology Of Hpimentioning
confidence: 99%
“…Furthermore, a prevalence of 64.6% in children with risk factors of overcrowding, patronizing of food vendors, and illiteracy was reported in Egypt [36]. In the Republic of Benin, a 71.5% prevalence rate was reported but was not associated with age, sex, marital status, religion, occupation, or education [37]; 73.2% in Cameroon with a significant association with age, socioeconomic status, alcohol, family history, and nonsteroidal anti-inflammatory drugs and similarly anemia, duodenal ulcer, and chronic gastritis have been reported as common in patients with H. pylori infection [38]; and 71.43% prevalence rate was published in Algeria [39]. In a research conducted in Ethiopia, 88.9% H. pylori prevalence was reported in male individuals, while 82.8% was in female individuals [40].…”
Section: Epidemiology Of Hpimentioning
confidence: 99%
“…20,24 Meanwhile, the study of Agbor et al and Kpossou et al found a similar HPI prevalence in both gender. 21,23 These differences observed could be explain by the sample size and the study population. Furthermore, these differences may be due to improvement in the socioeconomic and hygiene conditions of the population over time according to.…”
Section: Discussionmentioning
confidence: 98%
“…22 Despite the small sample size, several studies conducted in SSA show the large representation of the females than the males. 21,23 The rate of antibodies anti-H. pilory (IgG) was 66.90% (95/142). In comparaison to other studies conducted in Cameroon, this result is higher than that found by Agbor et al 21 and similar to that found by Laure Brigitte et al 24 who reported a HPI seroprevalence of 43.4% (217/500) and 64.39% (132/205) respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence data published between 2014 and 2020 in Burundi, Rwanda, Congo-Brazzaville, and Cameroon have been reported to be 70.8%, 75%, 93.1%, and 73.2%, respectively [22][23][24][25]. Regions in West Africa, including Nigeria, Ghana, Togo, and the Republic of Benin, have reported prevalence of 87.8%, 88%, 70.41%, and 71.5%, respectively [26][27][28][29]. Prevalence as high as 71.43% has been reported in Algeria, 63.8% in Morocco, and 64.6% in Egypt, all located in the northern part of Africa [30][31][32].…”
Section: Wg 1: Epidemiologymentioning
confidence: 99%